The song of Achilles - Miller, Madeline (2012)
Patroclus, an awkward young prince, follows Achilles into war, little knowing that the years that follow will test everything they have learned, everything they hold dear. And that, before he is ready, he will be forced to surrender his friend to the hands of Fate. Set during the Trojan War.
Includes a character glossary and additional section with author interview, information about the book and author essays.
Orange Prize for Fiction, 2012.
Keywords: Achilles -- (Mythological character) -- Fiction; Trojan War -- Fiction; Greeks -- Turkey -- Fiction; Troy (Extinct city) -- Fiction; Greece -- History -- To 146 B.C. -- Fiction; War fiction; Historical fiction